Effective CAR T-cell targeting of an MUC1 cleavage product - David D Smith; Benoit J Smagghe; Mark G Carter; Kevin R Yi; Jac-Leen S S Nash; Trevor J Grant; Dan S Miller; Scott T Moe; Michael J Nash; Natalie K Miller; Laura L Agarkov; Jacy P Marquez; et al. (Journal for ImmunoTherapy of Cancer)
Background We developed Chimeric antigen receptor (CAR) T cells targeting mucin 1 (MUC1)* (muk * (muk 1 star)), which is the tumor-associated growth factor receptor form of MUC1. Our antibody, MNC2, uniquely binds to MUC1* on cancer cells but does not bind to full-length MUC1, which is expressed on all normal epithelial cells. We tested the ability of the Tyr to Phe mutations in CD3ζ, known as “1XX”, to increase in vivo persistence and enable the recognition and killing of low antigen-expressing cancer cells.Methods We performed in vivo experiments comparing CARs with either 4-1BB or CD28 co-stimulatory domains, with or without the “1XX” Tyr to Phe mutations in ITAMs 2 and 3 of the CD3ζ signaling domain. All CARs were targeted to the tumor using the same huMNC2-scFv. To explore the sensitivity of each CAR, tumors comprising varying percentages of high MUC1* expressing cancer cells were xenografted. Further, wild-type low MUC1* expressing cells were engineered to fluoresce red while the cells engineered to express more MUC1* were made to fluoresce green. This experimental design allowed us to compare the sensitivity limits of the CARs against low versus high antigen-expressing cancer cells.Results At high dose, all the CAR T cells effectively killed high antigen-expressing tumors in the short term. However, only the CAR bearing the 1XX mutations inhibited tumor recurrence in long-term experiments. Interestingly, in animals treated with CARs bearing wild-type CD3ζ, tumor recurrence was driven by the low antigen-expressing cells. Only the CAR bearing 1XX mutations demonstrated the ability to kill low antigen-expressing tumors, even when administered at low dose. Post-sacrifice analysis showed that the CAR T cells with 1XX mutations persisted longer in vivo than either 4-1BB or CD28 CAR T cells with wild-type CD3ζ.Conclusions These results support that the combination of targeting MUC1*, the growth factor receptor form of MUC1, with a CAR T bearing the 1XX mutations in CD3ζ has therapeutic potential for the treatment of solid tumor cancers.